Case report: Enamel renal syndrome: a case series from sub-Saharan Africa - Roomaney, I. A.; Kabbashi, S.; Beshtawi, K.; Moosa, S.; Chothia, M. Y.; Chetty, M. (Frontiers in Oral Health, 2023)
Enamel Renal Syndrome (ERS) (OMIM # 204690) is a rare genetic condition characterised by hypoplastic amelogenesis imperfecta, failed tooth eruption, intra-pulpal calcifications, gingival enlargement and occasionally nephrocalcinosis. In this case series, we report on four unrelated patients with a confirmed molecular diagnosis of ERS (FAM20A pathogenic variants) from sub-Saharan Africa. The pathognomonic oral profile of ERS was mostly fulfilled in these patients, with the notable addition of an odontoma in one patient. The cases presented a spectrum of phenotypic severity both dentally and systemically. One patient presented with nephrocalcinosis and abnormal kidney function, one had reduced kidney size with normal kidney function, and two had no renal abnormalities. Patients presenting with the oral profile of ERS should receive a prompt referral to a nephrologist and a geneticist. They should receive long-term management from a multidisciplinary medical and dental team.